2015
DOI: 10.1021/acs.jpcc.5b07878
|View full text |Cite
|
Sign up to set email alerts
|

Surface Oxidation of Au(111) Electrode in Alkaline Media Studied by Using X-ray Diffraction and Infrared Spectroscopy: Effect of Alkali Metal Cation on the Alcohol Oxidation Reactions

Abstract: The effects of alkali meal cation on the surface oxidation and alcohol oxidation reactions on Au(111) have been investigated using surface X-ray diffraction and infrared spectroscopy. It is known that alkali metal cations strongly affect the alcohol oxidation reactions on Pt(111); however, the oxidation reactions on Au(111) do not depend on alkali metal cations. Infrared spectroscopy reveals the formation of adsorbed OH in LiOH and CsOH solutions below the second anodic peak at 1.3 V. This result indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…The weak dependence of j-E profile with alkali cations was reported previously 23,32,34 for ethanol electrooxidation in gold single crystals and for ethylene glycol or glycerol electrooxidation on poly-oriented surfaces.…”
Section: Cation Effect On High Order Cyclic Voltammogramssupporting
confidence: 66%
See 4 more Smart Citations
“…The weak dependence of j-E profile with alkali cations was reported previously 23,32,34 for ethanol electrooxidation in gold single crystals and for ethylene glycol or glycerol electrooxidation on poly-oriented surfaces.…”
Section: Cation Effect On High Order Cyclic Voltammogramssupporting
confidence: 66%
“…The weak dependence of j-E profile with alkali cations was reported previously 23,32,34 for ethanol electrooxidation in gold single crystals and for ethylene glycol or glycerol electrooxidation on poly-oriented surfaces. 30 Nakamura et al 34 observed, by infrared spectroscopy, the same OH adsorption rate at potentials below 1.30 V on Au(111) surface regardless the cation, however X-ray diffraction reveled a protective effect against surface roughening at high potentials, this protection being more effective in the presence of Li + than Cs + .…”
Section: Cation Effect On High Order Cyclic Voltammogramssupporting
confidence: 66%
See 3 more Smart Citations